Pengaruh Implementasi Akuntansi Berbasis Akrual Dan Sistem Pengendalian Internal Terhadap Kualitas Laporan Keuangan: (Studi Kasus Pada Badan Pengelolaan Keuangan Dan Aset Daerah Kabupaten Sikka) - Yuliana Anggreani Dua Delang Kolit; Elisabeth Yessi Da Rato; Amanda Yecci Noeng (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to determine the effect of the implementation of accrual-bassed accounting and internal control systems on the quality of financial reports in the Regional Financial and Asset Management Agency (BPKAD) Sikka Regency.The research method used in this study is quantitative. Data analysis using multiple linear regression analysis. The results obtained in this study are that partially the variable of accrual basis accounting implementation does not affect the quality of financial statements and the internal control system affects the quality of financial statements while simultaneously all independent variables affect 22.9% of the quality of financial statements while the remaining 77.1% are influenced by other variables that are not included in the independent variables in this study